2015
DOI: 10.1159/000382123
|View full text |Cite
|
Sign up to set email alerts
|

EPIMAG: International Cross-Sectional Epidemiological Psoriasis Study in the Maghreb

Abstract: Background: Psoriasis is a common skin disorder that is characterized by red plaques covered with silvery scales and is associated with considerable psychosocial impact. It has been described in several studies worldwide, but specific data from the Maghreb (Algeria, Morocco and Tunisia) are unavailable. Objectives: To characterize the frequency of new psoriasis cases and to describe the epidemiological and clinical profile of psoriasis in the Maghreb. Methods: A psoriasis working group for the Maghreb initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
(31 reference statements)
3
13
0
Order By: Relevance
“…a life experience involving a profound change in a person’s existence, had occurred 1 month before the onset of psoriasis in 72% of 179 patients. Overall, estimates of the rates of stress‐related psoriasis range from 26 to 88% in epidemiological studies . Additionally, patients who report high levels of psychological stress display more severe skin and joint symptoms than those with lower reported levels of psychological stress .…”
Section: Overview Of the Stress–psoriasis Associationmentioning
confidence: 99%
“…a life experience involving a profound change in a person’s existence, had occurred 1 month before the onset of psoriasis in 72% of 179 patients. Overall, estimates of the rates of stress‐related psoriasis range from 26 to 88% in epidemiological studies . Additionally, patients who report high levels of psychological stress display more severe skin and joint symptoms than those with lower reported levels of psychological stress .…”
Section: Overview Of the Stress–psoriasis Associationmentioning
confidence: 99%
“…Thirty‐nine studies, evaluating 32 537 patients, fulfilled the eligibility criteria (19 surveys, seven cross‐sectional studies, 12 case–control studies, one cohort study). The characteristics of the case–control and cohort studies are presented in Table ; the characteristics of the included surveys and cross‐sectional studies are presented in Tables S1 and S2 (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies surveyed 26 099 patients with psoriasis regarding their beliefs in the role of stress in their disease . On average, 46% of patients believed their disease was reactive to stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, prevalence of psoriasis varies across geographical locations and races. Research conducted in the Middle East showed that the incidence of psoriasis in Algeria, Tunisia and Morocco was estimated at 10.36, 13.26 and 15.04 per 1000, respectively [3]. The severity of psoriasis varies from scattered papules to generalized scaly plaques [4].…”
Section: Introductionmentioning
confidence: 99%